151k views
1 vote
Solve the following system of equations
-2x+y=1
-4x+y=-1

2 Answers

4 votes

Answer:

(1, 3).

Explanation:

-2x + y = 1

-4x + y = -1 Subtract :

-2x - (-4x) = 1 - (-1)

-2x + 4x = 2

2x = 2

x = 1.

Substitute x = 1 in the first equation:

-2(1) + y = 1

-2 + y = 1

y = 1 + 2

y = 3.

User YemSalat
by
5.1k points
3 votes

Answer:

x = 1

y =

Explanation:

-2x + y=1

-4x + y=-1

-2 (2) x + (2) y = (2) 1 (multilply by 2)

-4x + y=- 1

-4x + 2y = 2

-4x + y = -1

minus side by

y = 3

x =

User Lexis Hanson
by
4.8k points